Interesting case series of severe anemia with marrow suppression - P Jagruthi; R H Gobbur; A S Akki; M M Patil; S S Kalyanshettar; S V Patil (Wolters Kluwer Medknow Publications, 2020)
Background: Deficiency of vitamin B12 and folic acid is becoming common now- a- days because of food fads and poor ingestion of fruits and vegetables. Resulting in the re-emergence of megaloblastic anemia. Objectives: In this case series, we want to highlight the importance of vitamin B12 and folate deficiency as a cause of severe anemia in children. Materials and Methods: Eight children with severe (Hb< 8gm/dl) anemia, & positive peripheral smear (i.e. macrocytic red cell precursors) were included in the study. The study period was for 7 months (August 2019 to February 2020). Results: Severe anemia in all cases, 6 (75%) cases had dimorphic anemia, 2 (25%) cases had megaloblastic anemia. The diagnosis was confirmed by vitamin B12 & folic acid assay and bone marrow aspiration. The response to supplementation with vitamin B12 and folic acid was good. Incidentally, all the patients were girls in the adolescent age group. Conclusion: 1. There seems to be a trend towards increasing the incidence of preventable nutritional Vit.B12 and Folate deficiency esp. in adolescent girls. This may have adverse effects on the next generation once the lady bears a child. 2. Increasing protective diet like vegetable and fruit intake, (the essential micronutrient-rich diet) can prevent severe nutritional anemia.